PENGARUH PENAGIHAN PAJAK DENGAN SURAT TEGURAN DAN SURAT PAKSA TERHADAP KEPATUHAN WAJIB PAJAK BADAN DI KANTOR PELAYANAN PAJAK PRATAMA SEMARANG TENGAH SATU - Richa Wahyu Arumi; Yulianti . (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2014)
The Purpose of this research to examine taxpayer compliance. Model of taxpayer compliance is tested with tax collection with a letter of reprimand and forced letter. Specifically, this research examines, (1) the effect of the tax collection compliance with the letter of reprimand against corporate taxpayers, (2) the effect of the tax collection forced letter to taxpayer compliance.The variables used in this study is the collection of tax with a letter of reprimand, forced letter of tax collection and taxpayer compliance. The sample in this research is the Tax Office Primary Middle Semarang The period 2009 to 2013. Sampling method used in this study is purposive sampling method. The method of data analysis used in this study is quantitative method consisting of classical assumption test, multiple linear regression analysis, the coefficient of determination and hypothesis test that using the t test.The results of quantitative analysis using the t test is known that the variable tax collection with a letter of reprimand and a significant positive effect on tax compliance by entities 5,221> t table of values with a significant value of 0,000, the tax collection forced letter positive and significant effect of 2,380 > of value t table with a significant value of 0,021.